Researching detective pathways: opportunities and challenges - O'Neill, Martin (Introduction to policing research, 2024)
This chapter provides an overview of some of the challenges and opportunities in conducting research in a police training environment with a specific focus on detective training. The chapter begins by providing a description of detective training in the past and identifying the challenges and training approaches that the police service has traditionally used. The introduction of police reforms (2018) through police transformation and policing vision 2025 are acknowledged alongside the professionalisation agenda to have driven substantial change in police training and education. The chapter focuses on the challenges and opportunities in gaining access to police training stakeholders and participants. The importance and complexity of the police hierarchy are discussed, and the importance of negotiation access at several levels within the police organisation. Acknowledging the role of independent research and ethics in relation to data protection, this chapter aims to provide insight for new researchers into policing research and some of the considerations required to maximise successful data collection.